IMPROVING DIRECTIONS OF INTEGRATION OF HIGHER EDUCATION AND THE LABOR MARKET IN THE REGIONS - Hakkulov , Fazliddin (THE INNOVATION ECONOMY, 2023)
In this article, the formation and implementation of the employment policy coordinating the directions of socio-economic development of the regions of the country, the directions for the development of the processes of training highly qualified personnel based on the integration of higher education and the labor market, as well as the obstacles to the improvement and development of the management of these processes factors and ways to eliminate them are described.